Methodological issues affecting the study of fish parasites. II. Sampling method affects ectoparasite studies - Kvach, Yuriy; Ondračková, Markéta; Janáč, Michal; Jurajda, Pavel (Diseases of aquatic organisms, 2016)
In this study, we assessed the impact of sampling method on the results of fish ectoparasite studies. Common roach Rutilus rutilus were sampled from the same gravel pit in the River Dyje flood plain (Czech Republic) using 3 different sampling methods, i.e. electrofishing, beach seining and gill-netting, and were examined for ectoparasites. Not only did fish caught by electrofishing have more of the most abundant parasites (Trichodina spp., Gyrodactylus spp.) than those caught by beach seining or gill-netting, they also had relatively rich parasite infracommunities, resulting in a significantly different assemblage composition, presumably as parasites were lost through handling and 'manipulation' in the net. Based on this, we recommend electrofishing as the most suitable method to sample fish for parasite community studies, as data from fish caught with gill-nets and beach seines will provide a biased picture of the ectoparasite community, underestimating ectoparasite abundance and infracommunity species richness.
Keywords: Parasitic Diseases, Animal; parazitární nemoci u zvířat; Fish Diseases; zvířata; nemoci ryb; infestace ektoparazity; Cyprinidae; Ectoparasitic Infestations; Animals